Method for Suppressing AC Side Fault Feed Current of Flexible DC Distribution Network Based on Improved Bidirectional Thyristor. Issue 4 (May 2021) - Gao, Chao; Chen, Xianda; Li, Jiyu; Zhao, Guosheng; Liu, Jianwei; Lin, Yufeng
Abstract: In the flexible DC power distribution system, once the DC side fails, the converter's interior will be quickly affected by the AC side fault feed. In view of the shortcomings of the current fault feed suppression methods, an improved AC side fault feed suppression method based on the improved bidirectional thyristor is proposed. The simulation results show that the above method can suppress the impact of the feed current inside the AC side converter and limit the short-circuit current flowing into the bidirectional thyristor on the AC side.